THE IMPACT OF WAITING LINES ON CUSTOMER SATISFACTION IN TOURISM COMPANIES (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This qualitative research study explores the impact of waiting lines on customer satisfaction in the context of tourism companies. The objective of this study is to gain insights into the customers' perceptions and experiences while waiting in lines, and how these factors affect their overall satisfaction with tourism companies. The research adopts a comprehensive literature review to capture the richness and depth of customers' subjective experiences. The analysis focuses on understanding the factors that contribute to positive or negative waiting experiences, including the perceived wait times, the level of information provided during the wait, the demand variability, service capacity, technology integration, customers expectation, queue management strategies, employee commitment and attitude and the interactions with staff and other customers. The findings of this study highlight the importance of effective communication, appropriate facilities, and staff training, managing perceived waiting times, maintaining service quality, embracing technology, and offering alternative experiences in mitigating the negative effects of waiting lines. The implications of this research contribute to the development of strategies and best practices for tourism companies to optimize their customer service and experience management. By recognizing the significance of waiting lines and addressing customers' concerns, companies can foster positive customer perceptions, loyalty, and ultimately enhance their competitive advantage in the tourism industry.
Keywords: waiting lines; tourism; customers; satisfaction